The effect of vitamin K2 supplementation on coronary artery disease in a randomized multicenter trial. (3rd October 2022) - Hasific, S; Oevrehus, K A; Lindholt, J S; Mejldal, A; Dey, D; Auscher, S; Lambrechtsen, J; Hosbond, S; Alan, D; Urbonaviciene, G; Becker, S; Rasmussen, L M; et al.
Abstract: Background: Coronary artery calcification (CAC) and especially progression in CAC is a strong predictor of acute myocardial infarction (AMI) and cardiovascular mortality [1]. Observational studies suggest a protective role of vitamin K2 in the development of CAC [2]. Measurement of CAC score in Agatston Units (AU) is common practice, while novel software as AutoPlaque introduces new opportunities to measure coronary plaques [3]. Purpose: The aim of this double-blinded randomized multicenter trial is to investigate if vitamin K2 supplementation can reduce the progression of CAC in a population without known coronary disease. Methods: AVADEC is a multicenter trial investigating 389 participants randomized to vitamin K2 (720 μg/day) and vitamin D (25 μg/day) versus placebo with a 2-year follow-up from 2018–2019 [4]. The primary endpoint of AVADEC is change in aortic valve calcification. In this substudy, we examined the progression of CAC in participants with no prior coronary disease (no myocardial infarction and/or revascularization) at baseline. Secondary, the change in CAC was evaluated in two prespecified subgroups (low-risk: CAC score <400 AU and high-risk: CAC ≥400 AU at baseline). Non-contrast CT-scans were performed at baseline, 12 and 24 months of follow-up. Contrast CT-scans were performed at baseline and 24 months. CAC score was measured with established software and expressed in Agatston Units (AU). On contrast CT-scans, quantitative coronary plaque composition evaluations were performed by using Autoplaque. Moreover, events (AMI, revascularization and all cause death) were assessed. Results: 304 participants (male, mean age 71 years) with no prior coronary disease were identified. The intervention and placebo groups were similar in all traditional cardiovascular risk factors except familial predisposition for cardiovascular disease (14.4% vs. 6.7%, p=0.046). We found progression of CAC in both the intervention and placebo group from baseline to 24 month follow-up (203 AU vs. 254 AU, p=0.089) (Figure 1). The patients with CAC score <400 AU at baseline were equal in progression (77 AU vs. 81 AU, p=0.846). In patients with CAC score ≥400, the progression of CAC was significantly lower in the intervention group (288 AU vs. 380 AU, p=0.047). Yet, preliminary analyses of contrast CT-scans in 180 participants showed no difference in the progression of non-calcified plaque volume (10 mm 3 vs. 37 mm 3, p=0.276). In addition, the number of events was significantly lower in participants receiving vitamin K2 and D (1.9% vs. 6.7%, p=0.048). Conclusion: Patients with no prior coronary disease randomized to vitamin K2 supplementation had a non-significant reduction in CAC development over a 2-year follow-up period. High-risk patients with CAC ≥400 AU had a significantly lower progression of CAC. Additionally, vitamin K2 supplementation significantly reduced the risk of AMI, revascularization and all-cause death. Funding Acknowledgement: Type of funding sources: Foundation. Main funding source(s): Danish Cardiovascular Academy (2/3) and the Region of Southern Denmark (1/3).